DEFISIT NERVUS OLFAKTORIUS SEBAGAI FAKTOR RISIKO GANGGUAN MEMORI PADA LANSIA - Vincentius Henry Sundah,* Yuda Turana,*Yvonne Suzy Handajani* (NEURONA, 2016)
INTRODUCTION OLFACTORY DEFICIT BECOMES THE EARLY CLINICAL SIGN OF COGNITIVE FUNCTION IMPAIRMENT AMONG THE ELDERLY PEOPLE THIS RESEARCH FOCUSES ON SPECIFIC COGNITIVE FUNCTION IMPAIRMENT OF THE FRONTAL LOBE WHICH IS A REGION OF BRAIN THAT RESPONSIBLE WITH MANY FUNCTIONS INCLUDING OLFACTORY FUNCTION ATTENTION EXECUTIVE AND MEMORY COGNITIVE FUNCTION